EFEKTIFITAS PENERAPAN STRATEGI PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR - Dwi Rimayani; Endi Riyoko; Ali Fakhrudin (Universitas Negeri Medan, 2023)
Abstract: Effectiveness Of Applying Contextual Teaching and Learning Strategies to Learning Outcomes Grade IV Students of SDN 29 Pagar Alam . This study aims to determine the effectiveness of applying Contextual Teaching and Learning strategies to the learning outcomes of grade IV at SD Negeri 29 Pagar Alam. This study used an experimental method with the Nonequivalent Control Group Design approach. This study used a sample of 43 students grade IV using a Purposive Sampling technique from a total population of 197 student at SD Negeri 29 Pagar Alam. Collecting data using test techniques, observation, and documentation. Based on the result of the research, it means that the CTL (Contextual Teaching and Learning) strategy has an effective impact on the learning outcomes of grade IV student of SD Negeri 29 Pagar Alam, this can be seen Sig. = 0.011 is smaller than alpha (α) = 0.05; with a tcount value of 2.647 and a ttable value of 1.681. It turns out that tcount > ttable or 2,500 > 1,681, then reject then Ho is rejected and Ha is accepted.Keyword: Contextual Teaching and Learning, Learning Outcomes. Abstrak : Efektifitas Penerapan Strategi Pembelajaran Contextual Teaching and Learning Terhadap Hasil Belajar Siswa Kelas IV SDN 29 Pagar Alam. Penelitian ini bertujuan mengetahui efektifitas penerapan strategi pembelajaran Contextual Teaching and Learning terhadap hasil belajar siswa kelas IV SD Negeri 29 Pagar Alam. Penelitian ini menggunakan metode eksperimen dengan pendekatan Nonequivalent Control Group Design. Penelitian ini menggunakan sample 43 siswa dari kelas IV dengan Teknik pengambilan sample sampling purposive dari total populasi 197 orang siswa kelas IV di SD Negeri 29 Pagar Alam. Pengumpulan data menggunakan Teknik tes, observasi, dan dokumentasi. Berdasarkan hasil penelitian, disimpulkan bahwa strategi CTL (Contextual Teaching and Learning) berdampak efektif terhadap hasil belajar siswa kelas IV SD Negeri Pagar Alam, hal ini dapat terlihat Sig.= 0,011 lebih kecil dari alpha (α)= 0,05; dengan nilai thitung sebesar 2,647 dan nilai nilai ttabel sebesar 1,681. Ternyata thitung > ttabel atau 2,500 > 1,681, maka Ho ditolak dan Ha diterima..Kata Kunci: Contextual Teaching and Learning, hasil belajar.